Bovine anaplasmosis as a risk factor for retained placenta, mastitis, and abomasal displacement in dairy cattle - Scariot, Claudia Almeida; Scariot, Julian; de Souza Ramos, Inalda Angélica [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Calchi, Ana Cláudia [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP]; Costa, Márcio Machado; Kreutz, Luiz Carlos; Zanella, Ricardo; Vieira, Maria Isabel Botelho (Elsevier, 2023)
This study aimed to evaluate the frequency of IgG antibodies against A. marginale, the occurrence of this bacterium by qPCR, and the effect of bovine anaplasmosis as a risk factor for clinical cases of retained placenta, mastitis, and abomasal displacement in dairy cattle. For that 179 Holstein cows out of three dairy herds, in the municipality of Sertão, Rio Grande do Sul, Brazil. These cows were on farms that were vulnerable to risk factors that are crucial to susceptibility among these animals to this intracellular hemoparasite. The mean seropositivity for A. marginale from the periods evaluated was 54% on farm A, 69.4% on farm B, and 27.3% on farm C. Molecular diagnosis was performed with qPCR and the mean positivity for A. marginale among the cows on farms A, B, and C in December 2017 was 34.6% (67/179). Infected animals showed clinical cases of retained placenta (6.1%), mastitis (6.1%), and abomasal displacement (0.5%). The association between positivity for anaplasmosis and these clinical cases was assessed through the odds ratio. Our results show that females with a positive qPCR assay for A. marginale had 52.48 times increased probability (OR) to develop clinical cases of retained placenta and mastitis (P < 0.001). These clinical cases negatively impact the productivity of positive females. Thus, implementing preventive and prophylactic control measures to ensure the sanitary quality of the herds is needed to avoid losses due to morbidity and mortality and diminish the economic losses suffered by farmers.
Keywords: Bovine Anaplasmosis; Diseases; ELISA; Holstein cows; qPCR; Risk factor